Potency of Bacillus subtilis and Lysinibacillus Mixed With Silica Nano Particles and Carbon Fiber in Controlling Potato Leaf Blight Disease [Phytophthora infestans (Mont.) de Bary] - Hersanti Wartono; Fitri Widiantini; Kirana Sonya Harviana (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2019)
Leaf blight disease caused by Phytohthora infestans is one of the major diseases on potato plant. To control the disease farmers usually use synthetic fungicides. However, the excessive use of synthetic fungicides may cause negative impacts on the environment. One of the alternative control methods which is more environtmentally friendly is the use of antagonistic microbes. In this experiment, Bacillus subtilis and Lysinibacillus sp. were formulated with carbon fiber as a carrier and enriched with nano silica as a micro nutrient, to find out the ability of the bacteria in suppressing leaf blight disease on potato plant. The experiment was carried out in the experimental field in Lembang, Bandung Barat, Jawa Barat. The experiment was arranged in the randomized block design consisted of nine treatments and four replications. Density of B.subtilis and Lysinibacillus sp. were 1011 cfu/ml. The formulation was applied 3 times, on planting, 2 weeks and 4 weeks after planting. The results showed that the application of B. subtillis and Lysinibacillus sp. were able to suppress leaf blight disease, with the disease inhibition 36,6% and 32,7% respectively. The combination treatment of B. subtilis in silica nano and carbon fiber was able to suppress leaf blight disease on potato plant higher compared to the application of bacteria without nano silica and carbon fiber, with the disease inhibition up to 51,2%.